THE RELATIONSHIP OF STRESS AND LEADERSHIP ON FEMALE VOLEYBALL (Fiep Bulletin - online, 2015)
The leadership and stress are important factors to coaches in the process of training and performance of their teams. This Study has the objective to analyze the relation between leadership and stress in 47 athletes of volleyball of base categories of Paraná Clube, with age (x= 14,7 and s.d.= 1,59).  It was used a Pearson correlation to leadership and stress with a significant level of p
Keywords: Volleyball; Leadership and Stress.